Pemberdayaan kelompok perempuan dalam pencegahan stunting melalui diversifikasi pangan lokal di Desa Ulu Sawa, Konawe Utara - La Ode Liaumin Azim; Pitrah Asfian; Lade Albar Kalza; La Ode Ahmad Saktiansyah; Agnes Mersatika Hartoyo; Kamrin Kamrin (Tintamas: Jurnal Pengabdian Indonesia Emas, 2026)
Stunting remains one of the nutritional issues that requires serious attention because it impacts physical growth, cognitive development, and the quality of human resources. One preventive measure that can be implemented at the community level is to empower mothers’ groups through local food diversification. This community service activity aims to improve mothers’ knowledge about stunting prevention through the diversification of local foods in Ulu Sawa Village, North Konawe. The methods used include education and mentoring for groups of mothers through outreach sessions on stunting, the importance of balanced nutrition, and the utilization of local foods as a source of nutritious food for children and families. Evaluation was conducted using pre-tests and post-tests to measure changes in participants’ knowledge levels before and after the activity. The results of the community service program showed an increase in mothers’ knowledge following the program’s implementation. These results indicate that the implemented community service program was effective in increasing mothers’ knowledge of stunting prevention. Thus, empowering mothers’ groups through the diversification of local foods can serve as a relevant and sustainable strategy in supporting efforts to prevent stunting at the village level.